PREVALENSI ANAK BERKESULITAN BELAJAR MEMBACA (DISLEKSIA) DI SEKOLAH DASAR INKLUSI - ANDAR SARI, ELISTA (Jurnal Pendidikan Khusus, 2016)
Abstract Reading difficulty is known as dyslexia is a disorder be caused by a dysfunction minimal of brain that can impact reading ability. In Surabaya City, prevalence of dyslexic children had not been known. Moreover, data of prevalence functions as projector to designs estimate of education needs for special need children, especially dyslexic children. Therefore, the aim of this research was to investigate the prevalence of dyslexic children. This research was using quantitative descriptive method by cross sectional study design. In addition to using research method, this research was also using area random sampling to decided research sample, using questionare, documentation, and test technique to gathered data, and using descriptive statistics with percentage formula (P=n/f x 100 %) to analysed data that was collected. A result of the research revealed that prevalence of dyslexic children in inclusion elementary school in  Surabaya city was 0,96 %. That is mean, 1 of 104 inclusion elementary school’s student  was dyslexic child.   Key word: Prevalence, Dyslexia